STRATEGI PEMBELAJARAN PAI MENGGUNAKAN E-LEARNING PADA MASA COVID-19 DI MAN 1 KOTA MALANG - Diana Islamia; Rosichin Mansur; Zuhkhriyan Zakaria (VICRATINA, 2021)
Technology is developing so rapidly that it has penetrated the world of education. Educational institutions must continue to adapt to technological developments because the object of education is students who are the next generation of the nation. During a pandemic like this, students are forced to study from home by online learning to using e-learning platforms. This is the background behind MAN 1 Malang City to use the e-learning platform in the process of each subject, including PAI lessons. This study was conducted at MAN 1 Malang City using research with a qualitative approach with the methods of observation, interviews and documentation. Where the use of this platform cannot be separated from technology and internet networks. The use of this platform is to maximize the PAI learning process as a medium and teaching material in order to arrive at perfect learning goals and of course according to the needs of students, communities and institutions. All forms of learning strategies have obstacles in their application. Likewise, this e-learning platform has factors that support and hinder its implementation even though it is very effectively used during Distance Learning.